INFORMATION ACTIVITY OF THE AIR TRAFFIC SERVICE OF UKRAINIAN STATE ENTERPRISE - BEM, Natalia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article is devoted to the main direction of information activity of the Ukrainian State Air Traffic Services Enterprise - air traffic safety. From this point of view, the article considers the work of the press center of the enterprise; analyzed press releases of UkSATSE management; rating reports on the work of Ukrainian airports prepared by UkSATSE. Important areas of work, such as the intensification of innovation, the introduction of information security systems, providing areas of work aimed at the fullest satisfaction of consumer needs are inextricably linked with the effectiveness of information activities. UkSATSE is interested in obtaining reliable information about the state of the company, the aviation industry in general, and about the most effective tools used by the world's leading companies in the field of air safety. The official website of UkSATSE defines the mission of the company, which is to provide quality and safe air navigation services in the airspace of Ukraine and in the airspace over the high seas, where the responsibility for air traffic services under international agreements rests with Ukraine. On the company's website you can see the full range of measures aimed at improving air safety. The press center is making significant efforts to inform the public about the company's activities aimed at developing air safety. Among its tasks: communication with the media, collecting information from the press, preparation of materials for professional sites, promotion of the company in the direction of Europeanization / The company's image is developing. The introduction of corporate identity of the enterprise is an important component of information and communication activities. "Safety", "efficiency", "responsibility" - key concepts for UkSATSE specialists under any conditions.